PENGUATAN LITERASI MASYARAKAT TENTANG BAHAYA HUMAN TRAFFICKING DI DESA BERAKIT, KABUPATEN BINTAN - Azhari Setiawan; Azrul Asyikin; Ryan Anggria Pratama; Okky Rizki Azizi; Adhe Fadli Farhan (Community Services and Social Work Bulletin, 2025)
The Community Service Program of Expertise of the Riau Islands Dekranasda is a strategic collaboration between Raja Ali Haji Maritime University and the Regional National Crafts Council of the Riau Islands Province. The main objective of this activity is to strengthen the capacity of MSMEs in the downstreaming of creative economy-based tourism products through increasing legal literacy, Intellectual Property Rights certification, and public policy advocacy. The implementation method uses a participatory approach through a policy dialogue forum and technical assistance for IPR registration. The results of this activity show a significant increase in participant knowledge (the average score increased from 4.58 to 4.71) as well as increased legal awareness and business motivation. The policy forum also produced strategic recommendations for strengthening the role of MSMEs in tourism development planning. This article discusses the academic-government-community (pentahelix) collaboration model in promoting the legitimacy and competitiveness of local products in the maritime region.